2016
DOI: 10.1016/j.cemconcomp.2015.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Milling as a pretreatment method for increasing the reactivity of natural zeolites for use as supplementary cementitious materials

Abstract: This work examined the effects of milling using a gravity ball mill on the reactivity of natural zeolites used as supplementary cementitious materials (SCMs). Six different particle size distributions of zeolites, created by milling the as-received zeolite in a ball mill for a specified amount of time, were characterized using x-ray fluorescence, quantitative x-ray diffraction, particle size analysis, pore size distribution and surface area analysis. Following material characterization, the pozzolanic reactivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 35 publications
1
22
0
10
Order By: Relevance
“…Burris and Juenger [25] showed that treating natural zeolites with acids dealuminates them, increasing surface area and thus pozzolanic reactivity (as measured by calcium hydroxide consumption). Likewise, milling zeolites decreases particle size, increasing filler effects and pozzolanic reactivity [26]. The high internal surface area of zeolites also provides unique opportunities for improved concrete performance, such as enhanced internal curing to reduce autogenous shrinkage [27] or self-healing of cracks [28].…”
Section: Waste Glassmentioning
confidence: 99%
“…Burris and Juenger [25] showed that treating natural zeolites with acids dealuminates them, increasing surface area and thus pozzolanic reactivity (as measured by calcium hydroxide consumption). Likewise, milling zeolites decreases particle size, increasing filler effects and pozzolanic reactivity [26]. The high internal surface area of zeolites also provides unique opportunities for improved concrete performance, such as enhanced internal curing to reduce autogenous shrinkage [27] or self-healing of cracks [28].…”
Section: Waste Glassmentioning
confidence: 99%
“…It was demonstrated that the combined use of liquid hot‐water treatment and biological pretreatment helps in the better enzymatic saccharification of Populus tormentosa . Details of all these methods are summarized in Table …”
Section: Conventional Pretreatment Methodsmentioning
confidence: 99%
“…Previous research indicates that the use of the raw form of these naturally occurring materials is technically not feasible. To cope with this issue, different treatment techniques were recommended such as mechanical grinding to produce the finest material, heating at elevated temperatures to get amorphous phases, and chemical treatment to develop more reactive products [25,26,27,28,29,30,31]. Due to the high cost of these methods, critical research is required to properly investigate all the potential naturally available materials in different parts of the world.…”
Section: Introductionmentioning
confidence: 99%